Premiumization strategy for Ben & Jerry's brand in the Czech and Slovak markets - Rosová, Sylvie (2023)
In the dynamic landscape of consumer preferences and competitive markets, premiumization has emerged as a critical strategy for brand differentiation and capturing consumer attention. This study focuses on Ben & Jerry's, a renowned ice cream brand, which faces challenges in maintaining premium perception and competing with rivals. By exploring premiumization in the Czech and Slovak ice cream markets, the research aims to enhance brand value and loyalty. The study encompasses theoretical insights into premiumization, consumer perceptions, and a two-phase research approach—qualitative interviews followed by quantitative questionnaire. The research reveals drivers of demand for premium products and barriers to paying a premium price. It offers five concurrent recommendations encompassing the 4Ps framework, intended to guide the brand's strategic decisions. This study contributes to knowledge on premiumization strategies, specifically tailored to Ben & Jerry's circumstances.